Antilisterial action of PLA films with ferulic acid as affected by the method of incorporation. (October 2022) - Ordoñez, Ramón; Atarés, Lorena; Chiralt, Amparo
Abstract: Previous studies demonstrated that polylactic acid (PLA) films with ferulic acid (F) obtained by melt blending did not release the active compound to exert effective antibacterial action. To solve this problem, different strategies to promote the active properties of PLA-F materials have been studied: film processing by casting with F up to 10% w/w, surface loading of thermoprocessed films with F, by adsorption or pulverisation with F solutions, and electrospinning of PLA-F solutions, using different solvent systems, to obtain nanostructured mats. The materials obtained were characterised by their morphological properties and antilisterial activity. F crystallised inside cast films and on the surface loaded PLA films. Electrospun materials exhibited different morphology, depending on the solvent system of the initial solution; fibre mats were obtained with ethyl acetate-DMSO mixtures, whereas bead structures were mainly formed with glacial acetic acid with or without ethyl acetate. No antilisterial activity was observed in cast films regardless of the F concentration, whereas surface loaded films by adsorption or pulverisation inhibited the listeria growth by about 4 Log (CFU/mL). Electrospun materials only inhibited bacterial growth (3 Log CFU) when these were fibre-structured. Therefore, active films of PLA with F could be only obtained when the active was surface anchored or encapsulated in thin fibre mats, with high surface to volume ratio. In this way, the release of the active compound is promoted, avoiding the problem of its limited internal diffusion through the PLA matrix. Graphical abstract: Image 1 Highlights: Alternative methods to incorporate ferulic acid (F) into a PLA matrix were studied. No bacterial inhibition was observed for cast PLA films with different concentrations of F. Film surface anchoring of F by adsorption or pulverisation provoked bacteriostatic effect. Fibre or bead formation in electrospun PLA-F materials depended on the used solvent. Fibre structured electrospun materials inhibited bacterial growth, unlike those bead-structured.